Epidemiology and complications of snakebite in rural area of Badin and Thar Sind, Pakistan - Asifa Jamali; Muhammad Yousif; Shahnawaz Kareem; Salam Ali; Beena Salman; Salman Imtiaz (Journal of the Pakistan Medical Association, 2022)
Objectives: To identify the population at risk of snakebite, the peak season and the site of bite. Method: The retrospective study was conducted at the Indus Hospital, Badin, Pakistan, and comprised data of patients bitten by snake between January 2017 and December 2020 in the rural area of the Sindh province who presented to the emergency room and were treated according to the institutional protocol. Data was collected on a structured proforma. Data was analysed using SPSS 21. Results: Of the 695 patients, 517(74.4%) were males and 178(25.6%) were females. The overall mean age was 29.9±15.7 years. Majority of the patients were farmers 294(42.3%), followed by labourers 195(28.1%). The most common site of snakebite was foot 556(80%). In 476(68.5%) cases, the snake type was not identified. Viper bite was noted in 193(28.2%) cases. Proteinuria, haematuria and renal dysfunction were observed in 302(43.5%), 302(43.5%) and 112(16.1%) patients, while leucocytosis, raised prothrombin time and low platelets were found in 305(43.5%), 268 (38.6%) and 100(14.4%) patients, respectively. Maximum number of cases took place in the peak summer month of July 112(16.1%). There were 8(1.2%) mortalities. Conclusion: Morbidity and mortality by snakebite was found to be prevalent in the study site, calling for preventing strategies. Key Words: Snakebite, Badin, Neglected disease, Prevention, Tropical area, Agricultural community, Pakistan.